Effect of geometric isomerism in dinuclear platinum antitumor complexes on DNA interstrand cross-linking - Kaspárková, J; Nováková, O; Vrána, O; Farrell, N; Brabec, V (Biochemistry, 1999)
The requirement for novel platinum antitumor drugs led to the synthesis of dinuclear bisplatinum complexes. To understand the molecular mechanisms underlying the biological activity of this new class of platinum cytostatics, modifications of natural DNA and synthetic oligodeoxyribonucleotide duplexes by dinuclear bisplatinum complexes with equivalent monofunctional coordination spheres, represented by the general formula [{cis-PtCl(NH(3))(2)}(2)(H(2)N-R-NH(2)](2+) (1,1/c,c), in which R is a linear alkane chain, butane or hexane, were studied by various biochemical and molecular biology methods. The results indicated that the major adducts of 1,1/c,c complexes in DNA ( approximately 90%) were interstrand cross-links preferentially formed between guanine residues. Besides 1,2 interstrand cross-links (between guanine residues in neighboring base pairs), 1,3 or 1,4 interstrand cross-links were also possible. In the latter two long-range adducts, the sites involved in the cross-links were separated by one or two base pairs. 1,2, 1,3, and 1,4 interstrand cross-links were formed with a similar rate and were preferentially oriented in the 5' --> 5' direction. In addition, the DNA adducts of these complexes inhibited DNA transcription in vitro. Thus, the binding of the 1,1/c, c complexes modifies DNA in a way that is distinctly different from the modification by the antitumor drug cisplatin. In addition, there are significant differences between the dinuclear 1,1/c,c and 1,1/t, t isomers. The results of this work are consistent with the hypothesis and support the view that platinum drugs that bind to DNA in a fundamentally different manner can exhibit different biological properties including the spectrum and intensity of antitumor activity. The intracellular DNA binding of the dinuclear compounds is compared to the results presented here. It has been suggested that differences in cross-link structure may be an important factor underlying their different biological efficiencies.
Keywords: genetická transkripce; Cross-Linking Reagents; stereoizomerie; Nucleic Acid Heteroduplexes; sekvence nukleotidů; oligodeoxyribonukleotidy; cisplatina; Cisplatin; Molecular Sequence Data; Transcription, Genetic; Circular Dichroism; molekulární sekvence - údaje; Antineoplastic Agents; reagencia zkříženě vázaná; Stereoisomerism; cirkulární dichroismus; Base Sequence; konformace nukleové kyseliny; protinádorové látky; heteroduplexy nukleové kyseliny; Nucleic Acid Conformation; Oligodeoxyribonucleotides; adukty DNA; DNA Adducts